2003
DOI: 10.1016/s0896-6273(03)00501-4
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Enhancement of Memory Storage and Synaptic Plasticity in Transgenic Mice Expressing an Inhibitor of ATF4 (CREB-2) and C/EBP Proteins

Abstract: To examine the role of C/EBP-related transcription factors in long-term synaptic plasticity and memory storage, we have used the tetracycline-regulated system and expressed in the forebrain of mice a broad dominant-negative inhibitor of C/EBP (EGFP-AZIP), which preferentially interacts with several inhibiting isoforms of C/EBP. EGFP-AZIP also reduces the expression of ATF4, a distant member of the C/EBP family of transcription factors that is homologous to the Aplysia memory suppressor gene ApCREB-2. Consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
190
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(198 citation statements)
references
References 63 publications
8
190
0
Order By: Relevance
“…Intriguingly, the Aplysia homologue of ATF4 has been referred to as a 'memory suppressor gene' 217 and mice with reduced ATF4 expression have enhanced hippocampal synaptic plasticity and memory storage. 218 Thus, interaction with ATF4 provides one possible mechanism by which DISC1 may modulate hippocampal function, aspects of which have been reported to be influenced by DISC1 genotype. 25 ATF5 is another cAMP-responsive transcription factor that interacts with DISC1.…”
Section: Disc1 Interaction With Atf4 and Atf5mentioning
confidence: 99%
“…Intriguingly, the Aplysia homologue of ATF4 has been referred to as a 'memory suppressor gene' 217 and mice with reduced ATF4 expression have enhanced hippocampal synaptic plasticity and memory storage. 218 Thus, interaction with ATF4 provides one possible mechanism by which DISC1 may modulate hippocampal function, aspects of which have been reported to be influenced by DISC1 genotype. 25 ATF5 is another cAMP-responsive transcription factor that interacts with DISC1.…”
Section: Disc1 Interaction With Atf4 and Atf5mentioning
confidence: 99%
“…Studies on a variety of different forms of synaptic plasticity have suggested a link between messenger RNA translation and learning and memory (Kandel, 2001). Phosphorylated eIF2a (p-eIF2a) reduces general protein synthesis, but facilitates the mRNA translation of the transcriptional modulator ATF4 (Harding et al, 2000), which inhibits synaptic plasticity and behavioral learning by repressing CREB activity (Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Protein synthesis is highly regulated at the level of initiation by numerous translational control molecules, including the eukaryotic initiation factor 2 (eIF2) (Sonenberg and Dever 2003). Although phosphorylation of the a subunit of eIF2 inhibits general translation, it selectively stimulates the translation of the transcriptional modulator activating transcription factor 4 (ATF4) (Vattem and Wek 2004), which plays a role as a repressor of cAMP response element-binding protein (CREB)-mediated synaptic plasticity (Bartsch et al 1995;Abel et al 1998;Chen et al 2003). Previously, it was shown that reduction of eIF2a phosphorylation in mice lacking the eIF2a kinase general control nonderepressible 2 (GCN2) and in heterozygous knockin mice with a mutation on serine 51 of eIF2a results in a lowered threshold for inducing long-lasting late-phase long-term potentiation (L-LTP) (Costa-Mattioli et al 2005.…”
mentioning
confidence: 99%